METODE CONTEXTUAL TEACHING AND LEARNING (CTL) PADA PEMBELAJARAN BE GOING TO VS WILL DI SMK NEGERI 2 MANADO - Mamiasa, Agnes B. B.; Warouw, Maya Pinkan; Pakasi, Jenny Hilda (Kajian Linguistik, 2017)
Contextual Teaching and Learning Approach (CTL) is one form of approach that can be said to be capable and very suitable to be a model of appropriate learning when applying the form of material in the classroom. Learning the form of CTL is closely related to the context, atmosphere or circumstances that can be interpreted also as learning related to a particular atmosphere. Talking about the atmosphere has to do with the use of the time form also known as tense. A little interesting about the Simple Future Tense that is raised to the core of learning because of this Tense became one of the important parts in the use of Grammar on learning English where we can express or declare actions in the future. This form uses the word 'will' and 'shall' (short form:’ll) plus infinitive. Besides using the form of 'going to' to be able to declare the time to come and the intention of the speaker to do something, for example I'm going to stop smoking '. CTL's role can make learning more effective and even create a fun and non-boring atmosphere, providing experiences that are closely related to the real world of learners and using a variety of learning resources; and therefore the method on CTL can provide understanding, development of science, the develop of knowledge and contextual understanding of learners about the relationship of subjects with what found learners in everyday life.Keywords : CTL, BE GOING TO vs WILL